# Zero is Zero Element for Natural Number Multiplication

## Theorem

Let $\N$ be the natural numbers.

Then $0$ is a zero element for multiplication:

- $\forall n \in \N: 0 \times n = 0 = n \times 0$

## Proof

Proof by induction.

For all $n \in \N$, let $P \left({n}\right)$ be the proposition:

- $0 \times n = 0 = n \times 0$

### Basis for the Induction

By definition, we have:

- $0 \times 0 = 0 = 0 \times 0$

Thus $P \left({0}\right)$ is seen to be true.

This is our basis for the induction.

### Induction Hypothesis

Now we need to show that, if $P \left({k}\right)$ is true, then it logically follows that $P \left({k + 1}\right)$ is true.

So this is our induction hypothesis $P \left({k}\right)$:

- $0 \times k = 0 = k \times 0$

Then we need to show that $P \left({k + 1}\right)$ follows directly from $P \left({k}\right)$:

- $0 \times \left({k + 1}\right) = 0 = \left({k + 1}\right) \times 0$

### Induction Step

This is our induction step:

\(\displaystyle 0 \times \left({k + 1}\right)\) | \(=\) | \(\displaystyle \left({0 \times k}\right) + 0\) | Definition of Multiplication | ||||||||||

\(\displaystyle \) | \(=\) | \(\displaystyle 0 + 0\) | Induction Hypothesis | ||||||||||

\(\displaystyle \) | \(=\) | \(\displaystyle 0\) | Definition of Addition |

By definition:

- $\left({k + 1}\right) \times 0 = 0$

So $P \left({k}\right) \implies P \left({k + 1}\right)$, and the result follows by the Principle of Mathematical Induction.

Therefore:

- $\forall n \in \N: 0 \times n = 0 = n \times 0$

$\blacksquare$